Atténuer l’impact des pratiques de pêche sur les écosystèmes par l’application du gradient de juridicité - Adélie Pomade (VertigO)
The increasing impact of fisheries practices on marine ecosystems and ecosystem services requires the mobilization of legal and societal instruments to correct the perverse effects they produce. Can public authority, through the law, freely interfere in the regulation of these practices to enable them to produce a virtuous effect on biodiversity, ecosystems and ecosystem services? Does it exist a threshold beyond which public authority must no longer act? It seems possible to answer these questions by applying the new conceptualized legal analysis tool called legal gradient. The unprecedented application of this tool is studied in a real-life laboratory which has long been used to study professional fishing practices that impacts biodiversity and ecosystem services: The Natural Marine Park of Iroise. After reviewing a situational analysis of practices and their impacts on biodiversity, ecosystems and ecosystem services, the article identifies main applicable instruments of positive law and societal regulations to account for their degree of effectiveness and efficiency. On this basis, the article then proposes to apply the legal gradient to envisage a new way of acting on practices, on the part of the public authority. This approach will be followed by a more theoretical reflection on the construction of the concept of governance.